Perforated ulcer post financial crisis 2002: increased incidence at Hospital Pasteur - Villanueva, Oscar; Diamant, Marcelo; Villarino, Alicia; Pereira Núñez, Diego; Villarino, Alicia (Cirugía del Uruguay, 2004)
The purpose of the paper is to demonstrate the intensification of perforated gastroduodenal ulcers and its connection with social and economic factors. With this aim in view, the authors proceeded to analyze the frequency of this pathology within the last 40 monts with a view to establish how it was linked to the evolution of social and economic factors arising from the financia/ crisis which occurred in 2002. Eighty-six patients were operated from January 2000 through April 2003, their mean age being 49 (16- 84); 70 of them (81,4%) men. lncrease in 2002 indicated a marked upsurge of 83,35% as campared to 2001 which was statistically significant. Thirty six percent of the patients had no previous history with these symptoms and consequently the perforation marked the onset of u/cer pathology. The negative trend of mu/tiple social and economic indicators during the same period shows, on the basis of existing literature on this subject, that there is a cause and effect relationship involved.